PENGOLAHAN ABON IKAN BANDENG DESA KARANGCANGKRING, KECAMATAN DUKUN, GRESIK (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2019)
Have done milkfish shredded manufacturing practices on Friday 25 January 2019 which implemented village meeting hall, Department of Fisheries results show the quality of the physical characteristics of milkfish shredded by organoleptic tests at a concentration of 1% turmeric IKN code 789 stating the color, aroma, texture and taste preferred by the panelists. As for the code 345 BON greatly affect the color, texture and flavor with turmeric concentration of 0.5%. YIT code 543 and 2% concentrations of saffron aroma is very influential on milkfish shredded